2022
DOI: 10.3389/fimmu.2022.957233
|View full text |Cite
|
Sign up to set email alerts
|

EGFR-targeted bacteriophage lambda penetrates model stromal and colorectal carcinoma tissues, is taken up into carcinoma cells, and interferes with 3-dimensional tumor formation

Abstract: IntroductionColorectal cancer and other adult solid cancers pose a significant challenge for successful treatment because the tumor microenvironment both hinders the action of conventional therapeutics and suppresses the immune activities of infiltrating leukocytes. The immune suppression is largely the effect of enhanced local mediators such as purine nucleosides and eicosanoids. Genetic approaches have the promise of interfering with these mechanisms of local immunosuppression to allow both intrinsic and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 130 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, M13 phages have also been engineered to target tumourous antigens, including epidermal growth factor (EGF) and carcinoembryonic antigen. 94 …”
Section: Therapeutic Potentials Of Virome: a Summary Of The Ongoing C...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, M13 phages have also been engineered to target tumourous antigens, including epidermal growth factor (EGF) and carcinoembryonic antigen. 94 …”
Section: Therapeutic Potentials Of Virome: a Summary Of The Ongoing C...mentioning
confidence: 99%
“…Interestingly, M13 phages have also been engineered to target tumourous antigens, including epidermal growth factor (EGF) and carcinoembryonic antigen. 94 Although preclinical animal model studies on phage therapies have shown promising results, there are several safety and regulatory concerns to address before extensive clinical applications (figure 2). Multiple early-phase clinical trials have reported that oral administration of phages is well tolerated in humans, [95][96][97] but these phages were administered in the context of a healthy gut.…”
Section: Phage Therapymentioning
confidence: 99%